The Impact of Green Credit Policy on Environmental Efficiency in the Chinese Regions (2007-2020) - Lu, Cheng (2023)
This study investigates the impact of the Green Credit Policy on environmental efficiency in China from 2006 to 2020. The research aims to extend the analysis period beyond previous studies and provide a more comprehensive understanding of the effectiveness of the policy. The findings reveal important insights regarding the policy's effectiveness in promoting environmentally friendly practices and sustainable development. Furthermore, the study highlights the significance of considering different channels of impact, such as enterprise innovation, industrial structure upgrades, and enterprise performance, in assessing the overall effectiveness of the Green Credit Policy. These findings contribute to the existing body of knowledge on the Green Credit Policy's impact on environmental efficiency in China. The study provides valuable insights for policymakers and stakeholders seeking to enhance the effectiveness of green credit policies and promote sustainable development.